Estimasi Dosis Radiasi Sinar-X Terhadap Efek Herediter Pada Radiografi Konvensional - Sylvia Ariska Susanti; Gusti Ngurah Sutapa; Maghfirottul Iffah (Universitas Hamzanwadi, 2022)
A study has been carried out on the estimation of X-ray dose on hereditary effects on conventional radiography. The research was conducted at the Bali Academy of Radiodiagnostic and Radiotherapy Engineering using a Raysafe X-Ray Multimeter. Secondary data was obtained in the form of results of checking the output voltage (kV), exposure time (ms) and exposure (mGy). The data obtained are then grouped according to the voltage used. The data is used to calculate the Entrance Surface Dose (ESD) value, which is then used to find the value of the Hereditary effect on the examination of each organ. In this study, the lowest ESD value was found at the use of a voltage of 40 kV, namely 0.3737 mGy, while the highest ESD value was at the use of a voltage of 80 kV, which was 0.7328 mGy. Based on the calculation of hereditary effects for generation I has the highest probability compared to generation II, this is very dependent on the ability of cells after exposure to radiation. Cells in general can make natural repairs. The longer the time after exposure to radiation, the more cells have the opportunity to repair the effects of radiation. So the probability of the risk of hereditary effects in generation II will be smaller.